2018
DOI: 10.1111/tops.12382
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Morality in 3‐D: Decision‐Making, Judgment, and Inference

Abstract: Humans face a fundamental challenge of how to balance selfish interests against moral considerations. Such trade‐offs are implicit in moral decisions about what to do; judgments of whether an action is morally right or wrong; and inferences about the moral character of others. To date, these three dimensions of moral cognition–decision‐making, judgment, and inference–have been studied largely independently, using very different experimental paradigms. However, important aspects of moral cognition occur at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 143 publications
(216 reference statements)
1
33
0
1
Order By: Relevance
“…In this regard, our model departs clearly from classic dual process models which propose that a fast, emotional, unconscious and automatic system is responsible for normative or deontological responses, while a slower and effortful reasoning process gives rise to contextual or utilitarian behaviors (12)(13)(14)(15)(16)(17)(18)(19)(20). To that extent, our model is more parsimonious and in tune with previous proposals suggesting that a single emotional system underlies moral judgment (11,29), and with recent discoveries showing that complex behaviors have their basis in dynamic coalitions of networks of brain areas, none of which should be conceptualized as specifically emotional or essentially cognitive (10,30,31).…”
supporting
confidence: 70%
“…In this regard, our model departs clearly from classic dual process models which propose that a fast, emotional, unconscious and automatic system is responsible for normative or deontological responses, while a slower and effortful reasoning process gives rise to contextual or utilitarian behaviors (12)(13)(14)(15)(16)(17)(18)(19)(20). To that extent, our model is more parsimonious and in tune with previous proposals suggesting that a single emotional system underlies moral judgment (11,29), and with recent discoveries showing that complex behaviors have their basis in dynamic coalitions of networks of brain areas, none of which should be conceptualized as specifically emotional or essentially cognitive (10,30,31).…”
supporting
confidence: 70%
“…First (and as shortly mentioned in the introduction), findings on moral reasoning in schizophrenic patients are inconsistent and not all findings support the notion of impaired moral decision making or ToM in patients [ 18 , 19 , 67 ]. Second, although current research allows a better understanding of impaired behavioral outcomes and neuroimaging studies provide interesting insight into the cortical regions involved, most studies focus on certain sub-aspects of moral reasoning which are rarely put into a more exhaustive framework or model [ 23 ] and future studies must show how these sub-aspects integrate into a full model of morality in psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of available studies is small, thus more research is needed to allow for conclusive meta-analyses. Second, the comparability of published studies is limited since not all experiments examine the same dimension of morality, which is assumed to consist of a) the moral decision itself, b) the moral judgment about how appropriate the action is and c) the moral inference describing how a person is perceived based on his/her action and additional information about the person [23]. Studies on SSD revealed evidence for impaired [13,14,17,22] as well as intact moral decision-making [13,[17][18][19]).…”
Section: Introductionmentioning
confidence: 99%
“…After attributing a value to each option under consideration, these functions weigh the likely benefits and costs resulting from an action. An option is selected based on maximizing this utility function (Yu et al, 2018). Different models have been used to compute utilities related to moral decisions (Box 1).…”
Section: Computations Of Utility Presiding Moral Choicesmentioning
confidence: 99%